1. PILKADA DAN DEMOKRATISASI DI DAERAH - Kushandajani, Kushandajani (Faculty of Social and Political Sciences Diponegoro University, 2008)
Election is the most importan for democracy. Election can make some contribution to political integration, linking te central government to local areas. The more fact of participating in an election and the associated task of learning party symbols and some facts about the party’s philosophy, may also facilitate national awarness among the polulation. But elections, like other political process in the developing countries, include Indonesia, are elite-driven.